Simultaneous measurement of multiple Th1 and Th2 serum cytokines in psoriasis and correlation with disease severity - Sharon E. Jacob; Mehdi Nassiri; Francisco A. Kerdel; Vladimir Vincek (Mediators of Inflammation)
Background: Psoriatic plaques have been shown to contain increased levels of proinflammatory cytokines. Serum levels of interleukin (IL)-6, IL-7, IL-8, and interferon (IFN)-γ have been reported elevated in psoriatic patients.